Air and sea transport: Competition strategies under normal and economic crisis environments - Rigas, Konstantinos; Sambracos, Evangelos; Gatzoli, Androniki (SPOUDAI Journal of Economics and Business, 2011)
Air and sea passenger transport were generally considered as serving different market segments with little competition between them. Recent research has however shown that the existence of a deregulated operating framework can lead to improved competition between the two modes. This article aims first to identify the circumstances under which air and sea transport compete. The second step is to further examine possible reactions to increase their competitive relationship. The Greek Aegean region presents an interesting case study due to its morphology and seasonal demand characteristics. The question on competitive strategies has become even more essential in an environment of economic crisis as that existing currently in the region. The comparison between air and sea transport presents an interesting and rare case in the transport field. It is mainly observed in the service of insular re- gions and is further defined by existence or absence of infrastructure. The cha- racteristics of these two modes, suggest that they will be operating in a more complementary role. While travelling by air has the advantage of speed, short- comings relate to volume and cost – the two main advantages of sea transport. Therefore even though these modes appear to “specialise” as far as freight is concerned, passenger travel comes up as common ground for the two. Even so, the traditional view is that these modes operate in different markets as they serve passengers with different needs and characteristics. A review of the literature re- vealed that the operating framework can play a role in this. The expected bene- fit of market deregulation is increased competition, which can lead to reduced fares, better frequency and service levels. This is not only limited in the scope of a single transport mode, but in many cases the effects are going to expand to other modes operating in the same area, thus affecting competition between modes as well. In this respect, an attempt is made to identify the circumstances under which air and sea transport can develop a competitive relationship. This paper embarks also on a discussion over possible strategies that these two modes can follow in order to increase their competitive position, especially in the cur- rent difficult conditions presented by the current economic crisis. An examina- tion of the market is conducted along with the results of a passenger survey in an attempt to address these issues. Greece’s geographical features and the importance of the islands indicate that the Aegean region could prove to be a common ground for competition between these two modes of transport. The transport needs of more than 200 inhabited islands are today served by a network of 24 airports and 90 seaports. Both po- pulation density and distance from the capital Athens vary. Demand for tran- sport services is highly seasonal, with the summertime peak period, fuelled mainly by tourism, being significantly higher. Therefore the Aegean provides a unique area to examine this situation, as it offers a rich and interesting mix of cases. The transport needs of the passengers were mainly covered through sea tran- sport, with air transport making its gradual appearance since the middle of last century. During the previous decades these two modes have operated in a hea- vily regulated environment, both covering specific market segments with almost no competitive relation between them. As of the 1990s, with the application of the EU transport policies promoting deregulation, these markets had to evolve. Deregulation in both markets has already some years behind it, with some early indications that it had succeeded in promoting competition within and to some extent between the markets. This process however has lately been affected by the difficult economic environment. JEL Classification: R41, R11, 018